PENGARUH KUALITAS PELAYANAN DAN AKSESBILITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA KANTOR POS (STUDI KASUS: KANTOR POS CABANG MUARA TEWEH) - Rae Shita; Amus (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2026)
This study aims to determine the effect of service quality and service accessibility on customer satisfaction at the Muara Teweh Branch Post Office. The study used a quantitative method with an accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The results showed that service quality and service accessibility simultaneously and partially have a significant effect on customer satisfaction. The most dominant variable influencing customer satisfaction is service quality. Therefore, improving customer satisfaction can be achieved through enhancing service quality and providing easier and more convenient service access.